Pola Makan Dan Tingkat Pengetahuan Gizi Terhadap Resiko Kejadian Obesitas Pada Remaja Di SMA Kristen 1 Tomohon. - I Made Djendra; Clift Christian Vincen Langi; Rudolf B. Purba (POLTEKKES KEMENKES MANADO, 2018)
Obest or obesity is the term used to show the accumulation of body fat that exceeds the normal limit. Excessive accumulation of body fat can often seem reluctant easily. People who are overweight are more receptive than normal weight people to external hunger cues, such as food taste and smell, or time to eat. Fat people tend to eat if they feel like eating, not eating when they are hungry. The type of research used was analytic observational research with cross sectional design. The population in this study were all students at Tomohon Christian High School 1 which was 1063 students. The sample was calculated in Slovak with a total of 43 students. Primary data is data about diet and the level of nutritional knowledge collected directly during the research. In this study most have a moderate level of knowledge with a total of 20 people (46.5%), a good level of knowledge of 20 people (32.6%), and less knowledge level of 9 people (20.9%).The results of the analysis using statistical test fisherexacttest with a value of p <0.05, which means there is a significant relationship between intake of levels of nutritional knowledge with obesity.